Systemy informacyjne wspomagające controlling jakości - Gubicz-Stachowiak, Dorota (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article briefly discusses the problem of control and quality and the role of the information in the Quality Controllership. Good information is the most important thing for the development. It is very important to know how and when to use information which is received. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 90-95